The Clausen function Cl_2(x) and its Related Integrals: Junesang Choi, Hari M. Srivastava - Team, Support (Thai Journal of Mathematics, 2014)
The Clausen function Cl_2(x) arises in several applications. A large number of indefinite integrals of logarithmic or trigonometric functions can be expressed in closed form in terms of Cl_2(x).The G-function introduced and systematically investigated by Barnes in about 1900, which was revived in the middle of the1980s in connection with the study of the determinants of the Laplacians, also has several useful and widely-spread applications.Here, in this paper, we aim at presenting some interesting definite integral formulas by using a known relationship between the Clausen function Cl_2(x) and the Barnes G-function.